The association of obesity and dengue severity in hospitalized adult patients - Yu-Yao Chiu; Chun-Yu Lin; Ling-Shan Yu; Wen-Hung Wang; Chung-Hao Huang; Yen-Hsu Chen (Journal of Microbiology, Immunology and Infection, 2023)
Background: Obesity is associated with unfavorable outcomes for infectious diseases. Most researches exploring the association between nutritional status and dengue severity have focused on pediatric populations, with only few studies assessing adult patients. Methods: Adult patients with laboratory-confirmed dengue admitted to a tertiary hospital in southern Taiwan between 2014 and 2015 were enrolled retrospectively. Demographics, comorbidities, clinical presentation, laboratory findings, and outcomes were obtained from case-record forms. Patients were categorized into obese group and nonobese group. The obese group comprised patients with a body mass index of ≥27.5 kg/m2. Results: A total of 1417 hospitalized patients with dengue were evaluated. The mean age was 57.9 years (range: 18–92 years). The obese and nonobese groups comprised 333 (23.5%) and 1084 (76.5%) patients, respectively. The obese group included more patients with hypertension (85%, p < 0.001), diabetes mellitus (33%, p < 0.001), and congestive heart failure (6.3%, p = 0.049). Multivariate analysis revealed that the obese group had more petechiae (AOR: 1.353, 95% CI: 1.025–1.786, p = 0.033), more dyspnea (AOR: 1.380, 95% CI: 1.015–1.876, p = 0.040), and more severe hepatitis (AOR: 2.061, 95% CI: 1.050–4.048, p = 0.036). The obese group also had higher peak hematocrit values (44.1%, p < 0.001) and lower nadir platelet count (45.3 × 103/μL, p = 0.049) than the nonobese group. Conclusion: In adult patients with dengue, obese group had more petechiae, dyspnea, severe hepatitis, lower nadir of platelet count, and higher peak hematocrit level. We observed no difference in severe dengue or mortality between obese and nonobese group.